PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI TERHADAP KINERJA ASN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA KANTOR DUPP KABUPATEN SITUBONDO - Iriansyah, Nur Arik; Arief, Mohammad Yahya; Soeliha, Siti (Fakultas Ekonomi dan Bisnis, 2022)
The purpose of the study was to determine the effect of transformational leadership and motivation on ASN performance with job satisfaction as an intervening variable at the DUPP office in Situbondo Regency. The sampling technique used in this study is probability sampling by taking proportionate stratified random sampling with the Slovin formula with a tolerable error rate of 10% as many as 73 people. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Transformational Leadership has a positive and significant effect on job satisfaction, Motivation has a positive and significant effect on job satisfaction, Transformational Leadership has a positive and significant effect on ASN Performance, Motivation has a positive but not significant effect on Performance ASN, Job satisfaction has a positive and significant effect on ASN Performance, Transformational Leadership has a positive and significant effect on ASN Performance through Job Satisfaction, Motivation has a positive and significant effect on ASN Performance through Job Satisfaction